Evidence of alterations of Beta-endorphin levels and Mu-opioid receptor gene expression in bipolar disorder. (October 2022) - Escelsior, Andrea; Sterlini, Bruno; Tardito, Samuele; Altosole, Tiziana; Magioncalda, Paola; Martino, Matteo; Serafini, Gianluca; Murri, Martino Belveri; Aguglia, Andrea; Amerio, Andrea; da Silva, Beatriz Pereira; Trabucco, Alice; et al.
Highlights: Beta-endorphins (β-END) and Mu-opioid receptors (MOR), have a crucial activity in affective modulation. The research on opioid system role in bipolar disorder is imited to small or anecdotal reports. Bipolar sujects showed an increased expression of MOR gene and decreased β-END levels. MOR gene is overexpressed during mania. Abstract: Despite the well-recognized effects of endogenous opioids on mood and behavior, research on its role in bipolar disorder (BD) is still limited to small or anecdotal reports. Considering that Beta-endorphins (β-END) and Mu-opioid receptors (MOR), in particular, have a crucial activity in affective modulation, we hypothesized their alteration in BD. A cross-sectional study was conducted. We compared: (1) BD type I (BD-I) patients ( n = 50) vs healthy controls ( n = 27), (2) two BD-I subject subgroups: manic (MAN; n = 25) vs depressed (DEP; n = 25) subjects. Plasma levels of β-END and MOR gene expression in peripheral blood mononuclear cells were analyzed using ELISA Immunoassay qRT-PCR. We found that subjects with BD exhibited a significant upregulation of MOR gene expression and a decrease of β-END ( p <0.0001 for both). MAN display higher MOR levels than DEP ( p <0.001) and HC ( p <0.0001). Plasma levels of β-END were lower in DEP compared to MAN ( p <0.05) and HC ( p <0.0001). The main limitations are the cross-sectional design and the lack of a group of euthymic subjects. Although preliminary, our results suggest a dysregulation of the endogenous opioid systems in BD. In particular, both MAN and DEP showed a reduction of β-END levels, whereas MAN was associated with MOR gene overexpression.